Optimalisasi Konsentrasi dan Disiplin Belajar melalui Pengenalan Teknik Pomodoro pada Siswa SMA Carnegie - Wily Julitawaty; Widalicin Januarty; Fitria Halim (CV. Armas Suan Sejahtera, 2026)
The development of digital technology has provided various conveniences in the learning process. It has also created challenges in the form of increased distractions that affect students’ learning focus. Low concentration levels and ineffective time management can reduce learning effectiveness and negatively impact students' academic productivity. One method that can help address these issues is the Pomodoro Technique, a time management method that divides learning activities into structured intervals of focused work and short breaks. This community service activity aimed to improve students’ understanding of the importance of concentration and learning discipline through the introduction of the Pomodoro Technique among students at Carnegie High School. The implementation method employed a participatory and educational approach through several stages, including preparation, material presentation, practical sessions, and evaluation. Evaluation was conducted through observation, discussions, and the administration of pre-tests and post-tests. The results showed that participants responded positively to the training activities. Students demonstrated high enthusiasm during the program and were able to understand and apply the Pomodoro Technique during learning simulations. In addition, the method was perceived as helpful in managing study time more effectively, improving concentration, and reducing boredom during learning activities. Therefore, the introduction of the Pomodoro Technique has the potential to serve as an alternative strategy for enhancing students’ concentration and learning discipline.